A psicanálise e o ato infracional - Bilotti, Camila Fernanda Coelho (2015)
The current research is characterized as a teorical and clinical study from Lacan and Freud´s orientation regarding infractional act and subjective transformations during adolescence. To investigate the relations between adolescence and transgression a person constitution, from 0 to 18 years old, will be presented. Fragments of police inquests which teenagers committed infractional acts will be taken to analyze the subjective process related with the law. It was sought investigate if there is a relation between transgression and adolescence through a study regarding both subjective constitution; from the investigation of law’s internalization and its relations with delinquent acts; and further analyses of interventional possibilities and treatment directions for young people in conflict with law. For psychoanalysis, during adolescence, the transgressional phenomenas are related with singular factors, with referential figures, and transformations during this period are related with the separation of the Other and sexualization. The care models offered, backed in rehabilitation practices, ends to be associated with punishment measures to adolescents. The clinic reflections shows the need to offer a space for hearing and to build up an individual that elaborates questions and be responsible of their acts